Muntingia calabura L Leaves Extract Inhibits Glucosyltransferase Activity of Streptococcus mutans - Rina Isnarianti; Ivan A. Wahyudi; Rini M. Puspita (Faculty of Dentistry, Universitas Indonesia, 2014)
Jamaican cherry (Muntingia calabura L.) is one type of plants that used by Indonesians as traditional medicine. Muntingia calabura L. leaves contain tannins, flavonoids, and polyphenolics that are believed to have capability as antibacterial agent. One of bacteria that can cause dental caries is Steptococcus mutans that has glucosyltransferase (GTF) which is capable to catalyze glucan synthesis in the progression of dental caries. Objective: To study the effect of 10% Muntingia calabura L. leaves extract toward S. mutans GTF activity. Methods: This research used 10% concentration of Muntingia calabura L. leaves, chlorhexidine gluconate 0.12%, and sterile distilled water, as the treatment, positive control and negative control group, respectively. GTF activity assays through fructose extensive area analysis by using High Performance Liquid Chromatography (HPLC). Fructose extensive area determined based on time retention from each groups. Fructose concentrations were expressed in percent (%) then converted into μmol/ml fructose that defined as a unit of GTF activity. The data was analyzed by one-way ANOVA. Results: One-way ANOVA analysis showed a significantly lower GTF activity in the treatment groupcompared to the negative control (p<0.05). Conclusion: 10% Muntingia calabura L. leaves extract capable to inhibit S. mutans GTF activity. DOI: 10.14693/jdi.v20i3.195